Consensus-Based Core Set of Outcome Measures for Clinical Motor Rehabilitation After Stroke—A Delphi Study - Pohl, Johannes; Held, Jeremia Philipp Oskar; Verheyden, Geert; Alt Murphy, Margit; Engelter, Stefan; Flöel, Agnes; Keller, Thierry; Kwakkel, Gert; Nef, Tobias; Ward, Nick; Luft, Andreas Rüdiger; Veerbeek, Janne Marieke (Frontiers in Neurology, 2020)
Introduction-Outcome measures are key to tailor rehabilitation goals to the stroke patient’s individual needs and to monitor poststroke recovery. The large number of available outcome measures leads to high variability in clinical use. Currently, an internationally agreed core set of motor outcome measures for clinical application is lacking. Therefore, the goal was to develop such a set to serve as a quality standard in clinical motor rehabilitation poststroke. Methods-Outcome measures for the upper and lower extremities and activities of daily living (ADL)/stroke-specific outcomes were identified and presented to stroke rehabilitation experts in an electronic Delphi study. In round 1, clinical feasibility and relevance of the outcome measures were rated on a 7-point Likert scale. In round 2, those rated at least as “relevant” and “feasible” were ranked within the body functions, activities and participation domains of the International Classification of Functioning, Disability and Health. Furthermore, measurement time points poststroke were indicated. In round 3, answers were reviewed in reference to overall results to reach final consensus. Results: In total, 119 outcome measures were presented to 33 experts from 18 countries. The recommended core set includes the Fugl-Meyer Motor Assessment and Action Research Arm Test for the upper extremity section; the Fugl-Meyer Motor Assessment, 10-Meter Walk Test, Timed-up-and-Go and Berg Balance Scale for the lower extremity section; and the National Institutes of Health Stroke Scale, and Barthel Index or Functional Independence Measure for the ADL/stroke-specific section. The Stroke Impact Scale was recommended spanning all ICF domains. Recommended measurement time points are days 2±1 and 7; weeks 2, 4 and 12; 6 months poststroke and every following 6th month. Discussion-and-Conclusions: Agreement was found upon a set of nine outcome measures for application in clinical motor rehabilitation poststroke, with seven measurement time points following the stages of poststroke recovery. This core set was specifically developed for clinical practice and distinguishes itself from initiatives for stroke rehabilitation research. The next challenge is to implement this clinical core set across the full stroke care continuum with the aim to improve the transparency, comparability, and quality of stroke rehabilitation at a regional, national, and international level.